Evaluating the outcomes and processes of a research-action partnership: The need for continuous reflective evaluation - Taylor, Chantal; Cockburn, Jessica; Rouget, Mathieu; Ray-Mukherjee, Jayanti; Mukherjee, Shomen; Slotow, Rob; Roberts, Debra; Boon, Richard; O’Donoghue, Sean; Douwes, Errol (African Biodiversity & Conservation, 2016)
Background: The KwaZulu-Natal Sandstone Sourveld (KZNSS) Research Programme is part of a collaborative, transdisciplinary research partnership between the University of KwaZulu-Natal and the eThekwini Municipality (EM), aimed at bridging the science-policy-practice gap. The research programme focuses on generating knowledge and capacity to support local land-use planning, management and policy development related to biodiversity and climate change issues.Objectives: The objectives were (1) to describe how a continuous reflective evaluation approach helped to better understand the research programme and its outcomes; and (2) to assess research outputs and outcomes, relevance of outcomes to the requirements of EM, and participants’ perceptions of the programme (both the outcomes and the process).Methods: The evaluation took a mixed methods approach, combining various quantitative and qualitative methods such as anonymous individual questionnaires, reflective exercises and group reflections.Results: The KZNSS programme was successful in capacity building and establishing a long-term partnership, but had lower scientific publication output and practice uptake than expected. Participants’ perceptions changed over time, with a decrease in the perceived success of addressing tangible research outcomes, and an increase in the perceived success of collaborative relationships in the partnership.Conclusion: Transdisciplinary partnerships can be a means of integrating research into policy and practice through knowledge exchange. An important lesson in the early stages of this partnership was to pay attention to the process and not only the outputs. The study highlights the importance of continuous participatory reflection and evaluation in such partnerships.